(untitled) (Huellas, 2023)
Agricultural activity increases productivity and profitability while increasing environmental costs. However if the sustainability of ecosystems is altered they will become degraded systems and will progressively stop providing services. This insufficiency will generate a reduction in the inherent capacity of ecosystems to sustain not only economic activity but also other human activities. The aim of this work is to evaluate the incidence of agriculturization on the provision of ecosystem services in the Environmental Units of Tandil, in the periods 1989-2004 and 2004-2019. Sustainability indicators adapted from the AgroEcoIndex Software were used to determine which are the landscape areas where the application of criteria related to environmental management is crucial. In particular the state of provision of biodiversity conservation services and the quality of soil and water is evaluated. The indicators used show a deterioration in the provision of these services of 29% and 11.48% respectively in the study period. It is essential to determine priority conservation areas, incorporate good agricultural practices and diversify control techniques beyond exclusively chemical control.